A rapid and accurate method for Helicobacter pylori detection via integrating LAMP assay with CRISPR/Cas12b detection by one-step in one-pot - Zhang, Yeqian; Liu, Tao; Zhang, Puhua; Ni, Bo; Wang, Xingang; Bai, Long; Sun, Wei; Guan, Yujing; Xia, Xiang; Cao, Hui; Gu, Jiayi (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionAccurate and timely detection of Helicobacter pylori (HP) is crucial for the diagnosis and management of gastritis and other HP-associated gastrointestinal disorders. Conventional diagnostic methods, such as PCR and culture, require specialized equipment and expertise, limiting their applicability in resource-limited settings. There is a pressing need for a rapid, cost-effective, and user-friendly diagnostic platform for HP detection, particularly in point-of-care settings.MethodsWe developed an integrated detection platform combining loop-mediated isothermal amplification (LAMP) with the CRISPR/Cas12b system in a single, one-step, one-pot reaction. The assay was optimized to function at a constant temperature of 58 °C and provides results within 45 minutes. The clinical performance of the system was evaluated using 22 clinical samples, and its diagnostic accuracy was compared with conventional PCR.ResultsThe LAMP-CRISPR/Cas12b assay demonstrated a limit of detection (LOD) of 14.77 copies per test, with no cross-reactivity observed against potential interfering nucleic acids, ensuring 100% specificity for HP. Clinical validation revealed a concordance rate of 90.91% (20/22) between the LAMP-CRISPR/Cas12b platform and conventional PCR, supporting the diagnostic reliability of the system.DiscussionThe integrated LAMP-CRISPR/Cas12b platform represents a promising alternative for the rapid and sensitive detection of HP. It combines the simplicity and rapidity of LAMP with the specificity of CRISPR/Cas12b, offering a robust, cost-effective, and high\-sensitivity diagnostic tool without the need for complex instrumentation. The method shows great potential for use in point-of-care testing (POCT) and could significantly enhance clinical practice by facilitating timely diagnosis and treatment of HP-related diseases.